1985
DOI: 10.1177/002224378502200404
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Country of Origin on Product Evaluations: A New Methodological Perspective

Abstract: A new methodological approach for examining the impact of country of origin on product evaluations is proposed. It takes the form of a multiattribute attitudinal model analyzed by means of a system of simultaneous equations. This approach makes possible examination of the impact of other attributes as well as country of origin on evaluations, and takes into consideration the effect of familiarity and knowledge about the product class. Differences between respondents of two different national origins are also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
274
3
13

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(301 citation statements)
references
References 9 publications
11
274
3
13
Order By: Relevance
“…We propose that country of origin does not only act as an informational cue, but also affects consumers' interpretation of advertising claims. This view extends the research of Johansson and colleagues (Erickson et al, 1984;Johansson et al, 1985), who showed that country of origin biases perceptions of product attributes. We use the term bsource effectQ to refer to the proposed moderating influence (cf., Goldberg & Hartwick, 1990).…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…We propose that country of origin does not only act as an informational cue, but also affects consumers' interpretation of advertising claims. This view extends the research of Johansson and colleagues (Erickson et al, 1984;Johansson et al, 1985), who showed that country of origin biases perceptions of product attributes. We use the term bsource effectQ to refer to the proposed moderating influence (cf., Goldberg & Hartwick, 1990).…”
Section: Introductionsupporting
confidence: 88%
“…They found for example that perceptions of cars' economy were biased upward for Japanese cars, while perceptions of the quality of the cars were biased upward for German cars. Johansson, Douglas and Nonaka (1985) build on this study and confirm that country of origin affects consumers' product attitudes by biasing their perceptions of particular attributes like gas mileage or driving comfort. The authors also find that this bias is stronger when product knowledge is low.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…The marketing literature also highlighted the role of national culture, more specifically, cultural distance or similarity between the host country and home country (i.e., country of origin effects). The main finding is that consumers prefer products from the countries with a relatively similar culture (e.g., Johansson et al 1985;Heslop et al 1998;Wang and Lamb 1983).…”
Section: International Competitiveness and International Marketingmentioning
confidence: 99%
“…The country-of-origin affects consumers' perceptions of product attributes (Erickson, Johansson, & Chao, 1984;Johansson, Douglas, & Nonaka, 1985). Consumers differentiate between products from different countries (Agrawald & Kamakura, 1999;Orth & Firbasová, 2003;Papadopoulos, Heslop, Graby, & Avlonitis, 1986;Verlegh & Steenkamp, 1999), a phenomenon known as the countryof-origin effect (Agrawald & Kamakura, 1999;Verlegh, Steenkamp, & Meulenberg, 2005).…”
Section: Introductionmentioning
confidence: 99%